Effect of different shade net on performance of fenugreek (Trigonella foenum-graecum L.) in summer season (Current Horticulture, 2024)
An experiment was conducted to assess the performance of leafy vegetable purpose fenugreek under different shade net under Saurashtra agro climatic zone of Gujarat during summer 2013-14 to 2015-16 at Agricultural Research Station (Fruit Crops), Junagadh Agricultural University, Mahuva. The experiment comprised five treatments consisting 50% green shade net, 75% green shade net, 50% white shade net, 75% white shade net and no shade net (open). The 75% white shade net produced highest plant height (14.13 cm) and green yield (1.13 kg/m2) of fenugreek. Thus, it is quite logical that higher yield of green fenugreek in summer season can be obtained by using 75% white shade net house under Saurashtra condition.